2010
DOI: 10.1055/s-0030-1267065
|View full text |Cite
|
Sign up to set email alerts
|

Open door expansive laminoplasty and postoperative axial symptoms: a comparative study between two different procedures

Abstract: Study design: Retrospective cohortObjective: To determine if there are differences in important clinical outcomes between patients treated with a “preservation of the unilateral posterior muscular-ligament complex (PMLC) procedure” and a “hinge side anchoring procedure (HSAP)” for the treatment of cervical spondylotic myelopathy (CSM).Methods: Nine hundred and forty-six patients underwent the above procedures for treatment of CSM between January 2006 and December 2009. Five hundred and fifty-two (58%) subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Preservation of the attachments of the nuchal muscles to the spinous process of the axis (the rectus major, inferior oblique, and semispinalis cervicis) and the muscle attachments to the spinous process of C7 (rhomboid and trapezius) protects postoperative cervical lordosis, ROM and decreases axial pain (18). The preservation of the unilateral nuchal, supraspinous and interspinous ligaments between C2-C7 is also important for the maintenance of cervical spinal lordosis and to lower the rate of postoperative axial neck pain (23). Reduced surgical exposure, no detachment of the muscle from the C2 and C7 spinous process and the restriction of the laminoplasty from C3 to C6 reduce postoperative kyphotic changes (2,17).…”
Section: █ Discussionmentioning
confidence: 99%
“…Preservation of the attachments of the nuchal muscles to the spinous process of the axis (the rectus major, inferior oblique, and semispinalis cervicis) and the muscle attachments to the spinous process of C7 (rhomboid and trapezius) protects postoperative cervical lordosis, ROM and decreases axial pain (18). The preservation of the unilateral nuchal, supraspinous and interspinous ligaments between C2-C7 is also important for the maintenance of cervical spinal lordosis and to lower the rate of postoperative axial neck pain (23). Reduced surgical exposure, no detachment of the muscle from the C2 and C7 spinous process and the restriction of the laminoplasty from C3 to C6 reduce postoperative kyphotic changes (2,17).…”
Section: █ Discussionmentioning
confidence: 99%
“…The C7-sparing technique preserved the C7 spinous process and its paraspinal muscular attachment, with only 3% of the patients complaining of post-AS [17], which was in contrast to 70% of patients reporting post-AS [18]. Cervical laminoplasty that can conserve the unilateral posterior muscular-ligament complex may lower the rate of post-AS [19]. In our study, the total incidence of post-AS after the single-door cervical laminoplasty was 40.2%.…”
Section: Discussionmentioning
confidence: 99%
“…32,87,92,105 Other reports just provided the incidence or percentage of postoperative kyphotic deformity. 4,28,67,107 Only 21 (20%) studies reported statistical comparisons between the preoperative and postoperative C2-7 angles.…”
Section: Postoperative Spinal Alignment and Deformitymentioning
confidence: 99%
“…9,15,41,42,45,46,81,87,97 Emphasis was placed on the semispinalis cervicis, which they tried to preserve 97 or repair. 5,74,110 Furthermore, they also tried to preserve muscles that attach to the spinous processes of C-7.…”
Section: Neck Painmentioning
confidence: 99%